Investing in Education: The Path to Prosperity in Vietnam - Khang, Nguyen The (Journal of Ecohumanism, 2025)
This study analyzes the impact of social investment in education on economic prosperity in Vietnam during the period 1998–2023 using an autoregressive distributed lag model. The results show that investment in education has a positive impact on economic prosperity in both the short and the long run. Meanwhile, labor has a complex relationship, with a negative but statistically insignificant impact in the long run but a positive short-term impact on economic prosperity. The long-run equilibrium coefficient reflects a fast adjustment speed of approximately 83.1%, bringing the economy back to equilibrium after shocks. This result affirms the essential role of education as a driver of prosperity and resilience in the Vietnamese economy, consistent with global evidence of the impact of human capital development on the economy. Policy recommendations include increasing education budgets, improving labor quality through vocational training, and promoting cooperation between education and businesses to enhance sustainable development and modernize Vietnam's economy.